2018
DOI: 10.3390/v10120717
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Vein Banding Virus P6 Protein Is a Translation Trans-Activator and Its Activity Can be Suppressed by FveIF3g

Abstract: The strawberry vein banding virus (SVBV) open reading frame (ORF) VI encodes a P6 protein known as the RNA silencing suppressor. This protein is known to form inclusion like granules of various sizes and accumulate in both the nuclei and the cytoplasm of SVBV-infected plant cells. In this study, we have determined that the P6 protein is the only trans-activator (TAV) encoded by SVBV, and can efficiently trans-activate the translation of downstream gfp mRNA in a bicistron derived from the SVBV. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Of these, studies regard to Lactobacillus [ 9 , 30 , 34 , 45 , 54 ], Lactococcus [ 26 , 62 ], Bifidobacterium [ 57 ], or Enterococcus [ 71 ] administration showed increased production of either IFN-α or IFN-β. Sixteen studies addressed the alteration of IFN-γ in respiratory virus infected mice administered with probiotics [ 26 , 33 , 39 , 48 , 51 , 52 , 54 58 , 69 , 71 74 ]. There are 12 studies declared the increase of IFN-γ after administration of probiotic Lactobacillus [ 30 , 32 , 33 , 39 , 48 , 51 , 52 , 54 , 55 ], Bifidobacterium [ 57 , 58 ], or Bifico [ 73 ] (a probiotic mixture consisting Bifidobacterium, Lactobacillus acidophilus , and Enterococcus ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, studies regard to Lactobacillus [ 9 , 30 , 34 , 45 , 54 ], Lactococcus [ 26 , 62 ], Bifidobacterium [ 57 ], or Enterococcus [ 71 ] administration showed increased production of either IFN-α or IFN-β. Sixteen studies addressed the alteration of IFN-γ in respiratory virus infected mice administered with probiotics [ 26 , 33 , 39 , 48 , 51 , 52 , 54 58 , 69 , 71 74 ]. There are 12 studies declared the increase of IFN-γ after administration of probiotic Lactobacillus [ 30 , 32 , 33 , 39 , 48 , 51 , 52 , 54 , 55 ], Bifidobacterium [ 57 , 58 ], or Bifico [ 73 ] (a probiotic mixture consisting Bifidobacterium, Lactobacillus acidophilus , and Enterococcus ).…”
Section: Resultsmentioning
confidence: 99%
“…Protein extraction and western blot hybridization were performed according to Li et al ( 2018 ). After transferring protein to nitrocellulose membranes, the membranes were probed with a mouse anti‐GFP or anti‐myc antibody and then probed with a horseradish peroxidase‐labelled goat anti‐mouse antibody.…”
Section: Methodsmentioning
confidence: 99%
“…The coding sequences of SVBV P1 (GenBank No: X97304.1) and FvLHC II-1L (GenBank No: XM_004303830.2) were cloned into pCV-cYFP and pCV-nYFP, respectively ( Li et al, 2018a ), to generate cYFP-SVBV P1, nYFP-FvLHC II-1L, nYFP-P1, and cYFP-FvLHC II-1L. The recombinant plasmids were transformed into A. tumefaciens (GV3101) and co-infiltrated into N. benthamiana leaves.…”
Section: Methodsmentioning
confidence: 99%
“…According to the proteins encoded by each ORF of CaMV, it was inferred that ORF II, III, IV, and V of SVBV may encode proteins associated with aphid infection, a DNA-binding protein, a coat protein (CP), a reverse transcriptase protein ( Pan et al, 2018 ). P6, encoded by ORF VI, is a multifunctional protein that functions as an RNA silencing suppressor and translation transactivator ( Li et al, 2018a ), and ORF VII encodes an unknown protein ( Schoelz et al, 2016 ). Our previous study showed that SVBV P1 may regulates intracellular and intercellular movement of SVBV during viral infection ( Rui et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%